Analysis of the Association of Urine Sodium Excretion and Serum Aldosterone with Clinical Outcomes. - Leonberg-Yoo, Amanda. (2017)
Abstract: The relationship between dietary sodium intake and clinically important outcomes remains controversial. Recent large observational studies have suggested a U-shaped relationship between sodium intake and kidney disease progression, cardiovascular disease, and all-cause mortality, with an increased risk of adverse events occurring in persons consuming high and low levels of sodium. We hypothesized that serum aldosterone, which has known vasculopathic properties, may be higher in individuals who consume lower amounts of sodium and may explain the association of low sodium intake with an increased risk of adverse outcomes. Using a case-cohort design in the Health Aging and Body Composition (Health ABC) Study, we assayed urine sodium, as a proxy for dietary sodium intake, and serum aldosterone. A subcohort (n=501) was randomly selected from the parent cohort of healthy individuals, and all additional cases who demonstrated progression of kidney disease, heart failure events, and cardiovascular events were added using the case-cohort method. We used linear regression to evaluate the association of urine sodium excretion and serum aldosterone at baseline. We used Cox proportional hazards to examine the associations of serum aldosterone levels and urine sodium levels with progression of kidney disease, incident heart failure, incident atherosclerotic cardiovascular disease (CVD), and all-cause mortality. We evaluated whether adjustment for serum aldosterone attenuated the relationship of urine sodium with these outcomes. The mean (SD) age of the Health ABC subcohort was 73.6 (2.8) years; 49% were women, and 61% were white. Sixty-four percent of the subcohort had hypertension, and 54% of these individuals were on antihypertensive medications. The mean (SD) estimated urine sodium excretion in the subcohort was 4,174 (1,546) mg/24 hours while median (25th, 75th) serum aldosterone was 5.12 (3.15, 8.85) ng/dL. There was an inverse relationship between urine sodium excretion and serum aldosterone; each 1 gram higher urine sodium excretion was associated with a 0.93 ng/dL lower serum aldosterone in multivariable adjusted analyses. In the entire case-cohort, there were 420 individuals who demonstrated progression of kidney disease, 220 incident heart failure events, 230 incident atherosclerotic CVD events, and 236 deaths. There was no association between serum aldosterone and progression of kidney disease, incident heart failure, or all-cause mortality in continuous or quartile models. Higher levels of serum aldosterone were associated with a lower risk of incident atherosclerotic CVD [HR per aldosterone doubling 0.85 (0.72, 0.99)] although the relationship was not linear. There was no association between increased urine sodium excretion and progression of kidney disease or all-cause mortality [HR per 1 standard deviation higher urine sodium 1.04 (0.89, 1.22) and 1.05 (0.92, 1.20) respectively], while lower levels of urine sodium showed a trend towards a higher risk of heart failure and atherosclerotic CVD [HR per 1 standard deviation higher urine sodium 0.92 (0.76, 1.10) and 0.87 (0.70, 1.08) respectively]. Serum aldosterone did not attenuate the relationship of low urine sodium with our principal study outcomes when examined as a continuous variable or according to quartiles. Lower levels of urine sodium were associated with higher levels of serum aldosterone. There was no consistent relationship between serum aldosterone with any of the clinical outcomes examined. Lower levels of urine sodium showed a trend towards higher risk of heart failure and atherosclerotic CVD. Serum aldosterone did not explain the relationship of low urine sodium with the outcomes under study. Further studies are needed to evaluate the mechanisms by which low urine sodium excretion may be associated with an increased risk of adverse outcomes.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: Mark Sarnak.; Committee: Hocine Tighiouart, and Lesley Inker.; Keyword: Medicine.